2017
DOI: 10.1109/tvcg.2017.2656889
|View full text |Cite
|
Sign up to set email alerts
|

Analytic Approximations for Real-Time Area Light Shading

Abstract: We introduce analytic approximations for accurate real-time rendering of surfaces lit by non-occluded area light sources. Our solution leverages the Irradiance Tensors developed by Arvo for the shading of Phong surfaces lit by a polygonal light source. Using a reformulation of the 1D boundary edge integral, we develop a general framework for approximating and evaluating the integral in constant time using simple peak shape functions. To overcome the Phong restriction, we propose a low cost edge splitting strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Switching between numerical and analytic evaluations according to some heuristics [Yuan et al 2012] might be potentially helpful. In addition, applying analytical approximations [Lecocq et al 2017] might make the gradient evaluations more efficient.…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…Switching between numerical and analytic evaluations according to some heuristics [Yuan et al 2012] might be potentially helpful. In addition, applying analytical approximations [Lecocq et al 2017] might make the gradient evaluations more efficient.…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…The area light is actually what we refer to as an LPAL. While real‐time rendering for scenes with area lights have been intensely studied [Arv95; Dro14; HDHN16; LDSM17], we employed the approach proposed by Heitz et al [HDHN16] because of its fast calculation and applicability to glossy surfaces. Following their method, we calculate the integration using the following formula:…”
Section: Indirect Illumination With Layered Polygonal Area Lightsmentioning
confidence: 99%
“…Considering a line parameterization along this straight line and assuming that the light contribution from a cutting section is a function of the line parameter, we found that the contribution from the slice of volume can be represented in an analytic form. Given that the cutting section of an emissive participating medium can be considered as an area light, we can compute its light contribution efficiently using modern approaches [HDHN16; LDSM17]. In this paper, we refer to these virtual area lights as layered polygonal area lights (LPALs).…”
Section: Introductionmentioning
confidence: 99%
“…The use of numerical methods to approximate integrals for accurate real-time rendering of surfaces lit by non-occluded area light sources leads to results with noise, hardly compatible with real-time rendering constraints [62].…”
Section: State Of the Artmentioning
confidence: 99%